The influence of internal factors on loan risk management - Case study commercial banks of Kosovo - Sahiti, Arben; Ramushi, Arbana Sahiti; Yurtsever, Hatice; Bekteshi, Sevdie Alshiqi (International Journal of Applied Economics, Finance and Accounting, 2023)
The main purpose of this study is to empirically analyse key internal factors influencing loan risk management of Kosovo’s commercial banks. This research adopts parametric statistics and employs a multilinear regression model. The data used for the analysis covers 7 banks for the 12 years from 2008 to 2019. The dependent variable is credit risk measured by dividing total debt by total assets. The independent variables are the size of the bank, the ratio of non-performing loans, the capital adequacy ratio, the debt-to-capital ratio, and asset management. The hypotheses raised in this research were tested through the SPSS software package using quantitative methodology. The results obtained through multiple linear regressions have shown that credit risk is positively correlated and statistically significant with non-performing loans and debt-to-equity ratio and statistically significant and negatively correlated with bank size, capital adequacy, and asset management. Considering our results, it can be considered that Kosovo’s commercial banks have performed very well so far by assessing internal factors that impact credit risk. The findings of this research have direct practical implications for the banking sector in Kosovo regarding the credit risk management approach because it can be used further to enhance the effectiveness of using proper mechanisms and regulations to minimize credit risk exposure.